Description of Nothacrobeles sohlenii sp. n. (Rhabditida: Cephalobidae) from Tunisia (Journal of Nematode Morphology and Systematics, 2012)
A new species ofNothacrobeles, N. sohlenii sp. n., is described from fine sand associated with roots of Indian Fig Opuntia (Opuntia ficus-indica) collected in the surroundings of Hammamet, Tunisia. It is characterized by a body length of 525-539 μm in females and 486-573 μm in males; lateral field with three incisures extending almost to tail terminus; three pairs of asymmetrical lips, pairs of lips separated by U-shaped primary axils with two triangular-acute guarding processes, and each lip asymmetrically rectangular with seven tines along its margin; three labial probolae, each bifurcated at two levels: once at about half of their length and again apically on each of the primary branches; labial probolae lacking additional tines; each labial probola with a basal ridge extending into rounded platelets on each side, and a basal abaxial concave ridge (ledge); pharyngeal corpus 1.9-2.1 times isthmus length; nerve ring and excretory pore at isthmus level; spermatheca 29-46 μm long; postvulval uterine sac 29-32 μm long; and two circular, cup-shaped pads observed by SEM on the surface of the everted cloaca, occurring on either side of the spicules. The new species has a unique set of characters in the lip region separating it from all other known species of the genus. It shows some esemblances to the previously described species N. borregi, N. laticollaris and N. subtilis.